2007
DOI: 10.1007/s11145-007-9092-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of derivational morphology in the reading comprehension of Spanish-speaking English language learners

Abstract: This study examined the relationship between morphological awareness and reading comprehension in English among Spanish-speaking English language learners (ELLs) followed from fourth through fifth grade. Students' ability to decompose derived words while reading was assessed using an experimental task. Multiple regression analyses were used to investigate the contribution of performance on this task to reading comprehension above and beyond word reading skills, phonological awareness, and breadth of vocabulary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
189
0
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(211 citation statements)
references
References 46 publications
(58 reference statements)
13
189
0
9
Order By: Relevance
“…However, there are also studies that showed that the degree of syntactic awareness in L1 was not transferred to L2 (Chiappe, Siegel & Wade-Woolley, 2002). Furthermore, several studies have shown that language components of L1, such as phonological, morphological and syntactic knowledge, spelling knowledge and vocabulary contribute to the understanding of L2 (Abu-Rabia & Bluestein-Danon, 2012;Abu-Rabia & Shakkour, 2014;Abu-Rabia et al, 2013;Kahn-Horwitz et al, 2005;Kieffer & Lesaux, 2008;Zhang & Koda, 2008). However, researches such as that of Akamatsu, (2003) found that there was no transfer of linguistic skills that would contribute to improving L2's reading comprehension.…”
Section: Research Findings On the Linguistic Skills Transfer Between mentioning
confidence: 99%
“…However, there are also studies that showed that the degree of syntactic awareness in L1 was not transferred to L2 (Chiappe, Siegel & Wade-Woolley, 2002). Furthermore, several studies have shown that language components of L1, such as phonological, morphological and syntactic knowledge, spelling knowledge and vocabulary contribute to the understanding of L2 (Abu-Rabia & Bluestein-Danon, 2012;Abu-Rabia & Shakkour, 2014;Abu-Rabia et al, 2013;Kahn-Horwitz et al, 2005;Kieffer & Lesaux, 2008;Zhang & Koda, 2008). However, researches such as that of Akamatsu, (2003) found that there was no transfer of linguistic skills that would contribute to improving L2's reading comprehension.…”
Section: Research Findings On the Linguistic Skills Transfer Between mentioning
confidence: 99%
“…Numerous research study findings indicate that linguistic components of L1, such as phonological awareness, morphological awareness, orthographic knowledge and meta-cognitive knowledge, all contribute to the development of reading and reading comprehension in a second language (Carlisle, Beeman, Davis, & Spharim, 1999;Cho & Tong, 2014;Gottardo & Mueller, 2009;Kahn-Horwitz, Shimron, & Sparks, 2005;Kieffer & Lesaux, 2008;Lefrançois & Armand, 2003;Lervåg & Aukrust, 2010;Nakamoto, Lindsey, & Manis, 2008;Nassaji & Geva, 1999;Nergis, 2013;Proctor, August, Carlo, & Snow, 2006;Pasquarella, Gottardo, & Grant, 2012;Protopapas, Sideridis, Mouzaki, & Simos, 2007;Van der Leij, Bekebrede, & Kotterink, 2010;Wang, Ko, & Choi, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…En las evaluaciones desarrolladas por los investigadores se encontraron efectos significativos de la intervención, los cuales se correlacionaban estrechamente con la intervención que medía el conocimiento de las palabras enseñadas y con la conciencia morfológica, con tamaños del efecto ( Además de enseñar explícitamente palabras en contexto, hay expertos en vocabulario como Michael Graves (2006) que enfatizan la importancia de la enseñanza de estrategias para la adquisición de nuevas palabras en un texto, tales como la conciencia morfológica y la conciencia léxica. El papel de la conciencia morfológica en la capacidad de comprensión lectora ha sido examinado por Kieffer y Lesaux (2008). En su trabajo, estos autores describen un estudio de intervención con estudiantes bilingües y monolingües de los cursos superiores de educación primaria a los cuales se les enseñó estrategias para fomentar la conciencia morfológica en el contexto de un plan de estudios de vocabulario destinado a mejorar las habilidades de comprensión lectora en inglés.…”
Section: Enseñanza Efectiva Del Vocabulariounclassified